STRATEGI PEMASARAN PRODUK SAYURAN DATARAN TINGGI DI WILAYAH KECAMATAN BATUR KABUPATEN BANJARNEGARA - Pujiharto Pujiharto; Sri Wahyuni (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2018)
The purpose of this study was to: analyze vegetable marketing strategies carried out by highland vegetable farmers; and analyze what factors influence the marketing strategy implemented by highland vegetable farmers. This research includes descriptive-quantitative research. The research location was carried out purposively in the Batur Sub District of Banjarnegara District. Data retrieval is done through surveys, observations and interviews using questionnaires. The unit of analysis was the farmer who planted the main highland vegetable plants in the study area (potatoes, cabbage, carrots). Data analysis was carried out in a quantitative descriptive manner with a Likert scale on the data of mastering marketing strategies. The strategy undertaken by highland vegetable farmers in product marketing on price, product, distribution and promotion indicators is low.